Solar Irradiation Estimations and Comparisons by ANFIS, Angström–Prescott and Dependency Models - Güçlü, Yavuz Selim; Yeleğen, Mehmet Öner; Dabanlı, İsmail; Şişman, Eyüp (Elsevier, 2014)
Solar irradiation calculations depend on atmospheric variations and sunshine duration record interval. Generally, it is calculated by using the classical Angstro¨m–Prescott equation, which provides a linear relationship between the solar irradiation and sunshine duration. Also few 2nd and 3rd degree solar radiation and sunshine duration models are proposed by different authors. Natural events do not have temporal and spatial independent structures. In this paper, three solar irradiation models are used for solar radiation examination in three of the southern cities, Adana, Antakya and Silifke in Turkey. One of these models are proposed in this work as dependency model and this is compared with the Angstro¨m–Prescott model and fuzzy logic ANFIS model. The comparison illustrates that dependency model is superior over other approaches.
Keywords: Solar İrradiation; Sunshine; ANFIS; Angström–Prescott; Temporal Dependency; Model